2018
DOI: 10.1002/humu.23549
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for GALNT12 as a moderate penetrance gene for colorectal cancer

Abstract: Characterizing moderate penetrance susceptibility genes is an emerging frontier in colorectal cancer (CRC) research. GALNT12 is a strong candidate CRC-susceptibility gene given previous linkage and association studies, and inactivating somatic and germline alleles in CRC patients. Previously, we found rare segregating germline GALNT12 variants in a clinic-based cohort (N = 118) with predisposition for CRC. Here, we screened a new population-based cohort of incident CRC cases (N = 479) for rare (MAF ≤1%) delete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…#112;80). This variant has been described several times, and although the role of GALNT12 in familial cancer is controversial, this particular variant most likely confers a moderate risk (Guda et al, 2009;Clarke et al, 2012;Seguí et al, 2014;Lorca et al, 2017;Evans et al, 2018). In EXO1 we identified the c.2212-1G>C variant in two individuals (no.…”
Section: Pathogenic and Likely Pathogenic Moderate And Low Risk Variantsmentioning
confidence: 92%
“…#112;80). This variant has been described several times, and although the role of GALNT12 in familial cancer is controversial, this particular variant most likely confers a moderate risk (Guda et al, 2009;Clarke et al, 2012;Seguí et al, 2014;Lorca et al, 2017;Evans et al, 2018). In EXO1 we identified the c.2212-1G>C variant in two individuals (no.…”
Section: Pathogenic and Likely Pathogenic Moderate And Low Risk Variantsmentioning
confidence: 92%
“…We selected 5 types of ppGalNac-Ts (GALNT2, GALNT3, GALNT6, GALNT12, GALNT14), as these ppGalNac-Ts have been reported to be closely associated with CRC. [27][28][29][30][31] Our analysis did not detect obvious differences in the mRNA levels of these ppGalNAc-Ts between Cosmc-overexpressing cells and the control cells ( Figure 4C). Collectively, these results suggested that aberrant O-glycosylation is unlikely the cause for Cosmc overexpression-mediated oncogenic alterations.…”
Section: Cosmc Overexpression-mediated Oncogenic Alterations Were Nmentioning
confidence: 63%
“…The di-glycosylated peptide sequence (Fig. 1 B ) is based on a previously optimized GalNAc-T12 peptide, T12_Pep (17), containing residues that uniquely enhance GalNAc-T12 activity, including Tyr at positions −3 and −2 (Y11 and Y12) N-terminal to the acceptor Thr at position 14 (T14) ( SI Appendix , Fig. S1 A ) and Arg at position +2 (R16) C-terminal to T14 (20, 23).…”
Section: Resultsmentioning
confidence: 99%
“…However, its expression is diminished in colon cancer cell lines and tissues from patients with CRC (15). Over the last decade, several studies in patients with CRC have led to the characterization of somatic and germ line mutations that reduce the in vitro enzymatic activity of GalNAc-T12 (1618). Many mutations occur in conserved residues, while a distinct subset alters nonconserved residues, suggesting the presence of GalNAc-T12–specific features ( SI Appendix , Table S1).…”
mentioning
confidence: 99%